As bibliotecas universitárias federais brasileiras e a acessibilidade das informações em seus websites The brazilians federal universities libraries and the information accessibility on its websites p.117-129 - Cortes, Márcia Della Flora; Lopes, Marilisa Leite (Revista ACB, 2008)
Resumo:Apresenta os resultados de pesquisa realizada com o objetivo de demonstrar a realidade, se houve evolução ou ampliação, de alguns serviços, produtos e recursos disponíveis nos websites das bibliotecas das Instituições Federais de Ensino Superior do Brasil. Com isso, constatou-se algumas falhas na prestação desses serviços, como a falta de alguns e até ausência de website da biblioteca. Bem como, discute-se a importância de as bibliotecas universitárias federais brasileiras investirem na disseminação das informações na web, a fim de torná-las acessíveis aos diversos tipos de usuários. Abstract:It presents the results of research carried through with the objective to demonstrate the reality, if it had evolution or magnifying, of some services, available products and resources in the Websites of the libraries of the Federal Institutions of Superior Education of Brazil. With this, one evidenced some imperfections in the installment of these services, as the lack of some and until absence of Website of the library. As well as, importance of the university libraries is argued it federal Brazilians to invest in the dissemination of the information in the Web, in order to become them accessible the diverse types of users.